Peran Bimbingan Islam Dalam Menangani Sifat Pesimis: (Studi Kasus Siswa-Siswi Di MA Darul Ulum Rampak Sana Laok Waru Pamekasan) - Toha, Moh.; B, Nurhasin; Hotimah, Nur (STAI Publisistik Thawalib Jakarta, 2022)
This study aims to determine: 1) How pessimistic students are, 2) How is the process of Islamic guidance in dealing with students' pessimism and 3) How is the impact of Islamic guidance on students' pessimism. The type of research used in this research is descriptive with a qualitative approach. Data collection methods used are interviews, observation and documentation. The results of the study concluded that 1) Madrasah Aliyah Darul Ulum Rampak Sana Laok Waru Pamekasan showed several characteristics of pessimism experienced by students including being unusually loud in front of many people, lack of socializing with other friends and lack of self-confidence possessed by students .2) The process of providing Islamic guidance is carried out in groups and sanctions are held for students who cannot change their pessimistic nature. 3) The process of providing Islamic guidance in the village of Sana Laok can actually change the character of students who initially have a pessimistic nature to become more optimistic and start trying to have high self-confidence.